Testing models of speciation from genome sequences: divergence and asymmetric admixture in Island South-East Asian Sus species during the Plio-Pleistocene climatic fluctuations - Frantz, Laurent A F (Mol Ecol, 2014)
In many temperate regions, ice ages promoted range contractions into refugia resulting in divergence (and potentially speciation), while warmer periods led to range expansions and hybridization. However, the impact these climatic oscillations had in many parts of the tropics remains elusive. Here, we investigate this issue using genome sequences of three pig (Sus) species, two of which are found on islands of the Sunda-shelf shallow seas in Island South-East Asia (ISEA). A previous study revealed signatures of interspecific admixture between these Sus species (Genome biology,14, 2013, R107). However, the timing, directionality and extent of this admixture remain unknown. Here, we use a likelihood-based model comparison to more finely resolve this admixture history and test whether it was mediated by humans or occurred naturally. Our analyses suggest that interspecific admixture between Sunda-shelf species was most likely asymmetric and occurred long before the arrival of humans in the region. More precisely, we show that these species diverged during the late Pliocene but around 23% of their genomes have been affected by admixture during the later Pleistocene climatic transition. In addition, we show that our method provides a significant improvement over D-statistics which are uninformative about the direction of admixture.